THE INFLUENCE OF “THE 1975 BAND” ON ENHANCING STUDENTS VOCABULARY MASTERY - Farhan Melsi Rahmatullah; Riswanto; Endang Haryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to find out the influence of using The 1975 Band songs on the vocabulary mastery of second-semester students of the 2025 cohort at UIN Fatmawati Sukarno Bengkulu. The 1975 Band songs were chosen as a learning medium because they contain various kinds of vocabulary, use authentic English, and can increase students' learning motivation. This research used a quantitative approach with a quasi-experimental method. The sample consisted of two classes, namely Class 2C as the experimental class and Class 2B as the control class, with 16 students in each class. The instrument used in this research was a multiple-choice test given in the form of a pre-test and a post-test to measure students' vocabulary mastery. The results showed a significant improvement in students' vocabulary mastery after the treatment. The average score of the experimental class increased from 56.75 to 91.25, while the average score of the control class increased from 65.50 to 78.06. These results indicate that there was a significant influence of using The 1975 Band songs on the vocabulary mastery of second-semester students of the 2025 cohort at UIN Fatmawati Sukarno Bengkulu. Therefore, The 1975 Band songs were proven to be an effective learning medium for improving students' vocabulary mastery.